Masjid Al-Ikhlas Kelurahan Bareng Kota Malang Sebagai Pusat Peradaban dan Kemakmuran Perspektif Konstruksi Sosial - Ardiansyah, Adistya Eka Sis (Prodi Sosiologi Agama, 2023)
The meaning of a mosque is not just a place of worship, but a place where civilization runs so that prosperity is needed in the mosque. This research aims to determine how the management process of the Al-Ikhlas Mosque, Bareng urban village, and Malang City is trying to reconstruct the true meaning of the mosque. The theory used in this study was the social construction of Peter L. Berger. This theory is useful for analyzing the social construction of the Al-Ikhlas Mosque in building civilization and the prosperity of the mosque through three processes: externalization, objectification, and internalization. This research uses qualitative methods with data collection techniques through observation, interviews, documentation, and relevant literature studies. The informants of this research were two mosque takmir administrators who were selected using a purposive sampling technique to ensure that the data generated were accurate. The results showed that there is a social construction in the management of the Al-Ikhlas Mosque, which is divided into three processes. The first is reflected in the response of the community, who needs a mosque as a center of civilization and prosperity for the people. Second, the objectification process through various mosque management activities such as the existence of the Happy Market, EkoMas (Al-Ikhlas Mosque Economy), Rukun Kematian, S3 (Sedekah Seribu Sehari), Sports Venue and routine studies. Third, the internalization process obtained by the community and mosque administrators through the primary socialization process from the family and secondary socialization from the surrounding environment, which is then passed down to the next generation, namely the mosque congregation, through routine studies. Through these three social construction processes, mosque management is created that aims to build a center of civilization and prosperity for the people.